Effect of acute complex training on upper-body force and power in collegiate wrestlers - Jones, M. T.; Oliver, J. M.; Delgado, J. C.; Merrigan, J. J.; Jagim, A. R.; Robison, C. E. (The Journal of Strength and Conditioning Research, 2019)
To determine if chain bench press (BP) exercise would enhance acute upper-body force and power, 13 collegiate male wrestlers (mean ± SD; 20.5 ± 1 years; 174.3 ± 4.2 cm; 76.5 ± 8.3 kg) with =1 year of strength training participated. Session 1 included body composition ([BodPod] 8.5 ± 2.6% body fat), 3 repetition maximum (RM) BP, and familiarization with the plyometric push-up (PPU) on a force plate. Athletes were matched for 3RM BP and randomly assigned to 1 of 2 groups: Chain BP or Plate BP. One week after session 1, athletes performed the experimental protocol that consisted of: Baseline PPU, Chain/Plate BP set 1 (6 reps @ 60%), 30 seconds rest, PPU, 3 minutes rest, Chain/Plate BP set 2 (6 reps @60%), 30 seconds rest, and PPU. Independent samples t-tests analyzed physical characteristics (p = 0.05). Standardized magnitude-based inferences were used to define outcomes. Aside from age (Plate BP 21.4 ± 0.8, Chain BP 19.9 ± 0.7 years), no physical differences were observed. Performance of Chain BP and Plate BP resulted in a likely (likelihoods of benefit/trivial/harm relative to the threshold for a smallest worthwhile benefit of 89 W: 0.5/9.2/90.3) and very likely (0.1/0.8/99.1) negative effect on peak power output in the PPU after set 1. Chain BP resulted in a likely positive effect on peak force in the PPU after set 1 (smallest worthwhile benefit 13 N: 82.8/16.9/0.3) and set 2 (94.7/5.2/0.1). Chain BP did not result in higher upper-body power over traditional plate loaded resistances.